2020
DOI: 10.1136/bmjgh-2019-001901
|View full text |Cite
|
Sign up to set email alerts
|

How men who have sex with men experience HIV health services in Kampala, Uganda

Abstract: In sub-Saharan Africa, men who have sex with men (MSM) are socially, largely hidden and face disproportionate risk for HIV infection. Attention to HIV epidemics among MSM in Uganda and elsewhere in sub-Saharan Africa has been obscured by repressive governmental policies, criminalisation, stigma and the lack of basic epidemiological data describing these epidemics. In this paper, we aim to explore healthcare access, experiences with HIV prevention services and structural barriers to using healthcare services in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 33 publications
0
29
0
Order By: Relevance
“…These factors act as barriers in accessing healthcare services by lesbian, gay, bisexual and transgender (LGBT) populations [27,38,39]. Furthermore, same sex relationships in sub-Saharan Africa are heavily stigmatized and criminalized in many countries in the continent [40,41]. Two studies conducted in Eastern Africa revealed that MSM encounter several barriers towards accessing health care services due to their sexual orientation.…”
Section: Sexual Health Care Deliverymentioning
confidence: 99%
See 2 more Smart Citations
“…These factors act as barriers in accessing healthcare services by lesbian, gay, bisexual and transgender (LGBT) populations [27,38,39]. Furthermore, same sex relationships in sub-Saharan Africa are heavily stigmatized and criminalized in many countries in the continent [40,41]. Two studies conducted in Eastern Africa revealed that MSM encounter several barriers towards accessing health care services due to their sexual orientation.…”
Section: Sexual Health Care Deliverymentioning
confidence: 99%
“…Two studies conducted in Eastern Africa revealed that MSM encounter several barriers towards accessing health care services due to their sexual orientation. These include being denied medications or provided with expired medications [27,41], and in some instances, addressed as mentally ill patients or as "psychotic" [41,42]. Because of the judgmental attitudes, discrimination, sociocultural and religious beliefs exerted by health care providers, MSM remain fearful in seeking health care services [27,[40][41][42][43].…”
Section: Sexual Health Care Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…A mathematical model suggests that the biggest reductions in HIV incidence in Sub-Saharan Africa will occur through increased coverage of HIV testing and effective treatment of people living with HIV (5). In Uganda, HIV testing uptake among men is low (55%) compared to 82% among women (6). No data are available regarding HIV testing coverage among MSM in Uganda where same sex relationships are criminalized through colonial-era laws (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…The Anti-Homosexuality Act was passed in 2014 but subsequently overturned by the Constitutional Court of Uganda (7,8). However, social and healthcare stigma and discrimination still hamper key population access to HIV prevention services (6) despite the fact that the Uganda Ministry of Health prohibits discrimination of key populations (7,8).…”
Section: Introductionmentioning
confidence: 99%